The Role of the Anterior Talofibular Ligament in Acquired Flat Foot Deformity and in the Operative Correction by Lateral Calcaneal Lengthening - Lukas Jud MD; Arnd Viehöfer MD; Sarvpreet Singh MD; Stefan Zimmermann MD; Tobias Götschi MSc; Dominic Rigling MD; Stephan Wirth MD (Foot & Ankle Orthopaedics, 2019)
Category: Hindfoot Introduction/Purpose: Different factors are well known influencing the development of adult acquired flatfoot (AAF) deformity. So far less attention was paid to the lateral ligament complex. The idea that the anterior talofibular ligament (ATFL) probably influences AAF could be obvious concerning its anatomical course. Goal of this study is to assess the influence of ATFL on AAF and on operative AAF correction by lateral calcaneal. Methods: We reviewed all patients that undergone lateral calcaneal lengthening in AAF from 01/01/2008 to 07/31/2018 in our clinic. Patients were grouped in patients with intact ATFL and in those with injured ligament. Two independent readers performed assessment of common radiographic flatfoot parameters in preoperative and postoperative radiographs. Results: Statistical significant difference between two groups could be observed for preoperative talonavicular uncoverage angle (p=0.018) and talocalcaneal angle (p=0.032), with more severe AAF in patients with injured ATFL. The other common radiographic parameters showed no significant difference, although a tendency to a more severe AAF could be observed within the group with damaged ATFL. No difference could be observed in surgical outcome or consistency after lateral calcaneal lengthening between two groups. Conclusion: ATFL seems to take impact in AAF concerning talonavicular uncoverage angle and talocalcaneal angle. In patients undergoing lateral calcaneal lengthening the integrity of the ligament seems not to influence the degree of correction or the consistency of the postoperative result.